Ranking Universities in Medan Using WoE and IV in Weighting of MAUT - Fadilah, Putri Maulidina; Perdana, Adidtya; Farhana, Nurul Ain (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Throughout Indonesia, including Medan, the popularity of a university can be specified by the ranking of a university. There are five assessment components which important for ranking universities under the Ministry of Education, Culture, Research, Technology and Higher Education, such as the Quality of Human Resources, Institutional Quality, Quality of Student Activities, Quality of Research and Community Service, and Quality of Innovation. Multi Attribute Utility Theory (MAUT) is one of the decision support system (DSS) methods that can be used to calculate campus rankings. However, the researcher were determining the weight of MAUT method based on their preferences and it was subjective. Weight of Evidence (WoE) can be used to assign a numerical score to each category of independent variables that describes the strength of its relationship to the target variable. In selecting the independent variable that is most informative and relevant in predicting the target variable, Information Value (IV) can be used. Based on the results, college B is the most popular university out of ten universities in Medan, with the highest evaluation value 0.796296296 using MAUT method and 0.923794719 using MAUT method with WoE & IV. The last position is J college with the lowest evaluation value 0.1666666667 for MAUT method and 0.02540176 for MAUT method with WoE & IV. The weighting of MAUT method with WoE and IV produces more optimal evaluation value than the the original MAUT method.